Quantitative performance evaluation of 124I PET/MRI lesion dosimetry in differentiated thyroid cancer. (19th December 2017) - Wierts, R; Jentzen, W; Quick, H H; Wisselink, H J; Pooters, I N A; Wildberger, J E; Herrmann, K; Kemerink, G J; Backes, W H; Mottaghy, F M
Abstract: The aim was to investigate the quantitative performance of 124 I PET/MRI for pre-therapy lesion dosimetry in differentiated thyroid cancer (DTC). Phantom measurements were performed on a PET/MRI system (Biograph mMR, Siemens Healthcare) using 124 I and 18 F. The PET calibration factor and the influence of radiofrequency coil attenuation were determined using a cylindrical phantom homogeneously filled with radioactivity. The calibration factor was 1.00  ±  0.02 for 18 F and 0.88  ±  0.02 for 124 I. Near the radiofrequency surface coil an underestimation of less than 5% in radioactivity concentration was observed. Soft-tissue sphere recovery coefficients were determined using the NEMA IEC body phantom. Recovery coefficients were systematically higher for 18 F than for 124 I. In addition, the six spheres of the phantom were segmented using a PET-based iterative segmentation algorithm. For all 124 I measurements, the deviations in segmented lesion volume and mean radioactivity concentration relative to the actual values were smaller than 15% and 25%, respectively. The effect of MR-based attenuation correction (three- and four-segment µ -maps) on bone lesion quantification was assessed using radioactive spheres filled with a K2 HPO4 solution mimicking bone lesions. The four-segment µ -map resulted in an underestimation of the imaged radioactivity concentration of up to 15%, whereas the three-segment µ -map resulted in an overestimation of up to 10%. For twenty lesions identified in six patients, a comparison of 124 I PET/MRI to PET/CT was performed with respect to segmented lesion volume and radioactivity concentration. The interclass correlation coefficients showed excellent agreement in segmented lesion volume and radioactivity concentration (0.999 and 0.95, respectively). In conclusion, it is feasible that accurate quantitative 124 I PET/MRI could be used to perform radioiodine pre-therapy lesion dosimetry in DTC.